2022
DOI: 10.3390/antiox11010144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Carotenoid Extract from Citrus reticulata By-Products on the Immune-Oxidative Status of Broilers

Abstract: Although carotenoids generally possess antimicrobial and antioxidant properties, the in vivo synergistic action of carotenoid blends derived from plant-based by-products has not been thoroughly studied. Therefore, the carotenoid characterization and antimicrobial potential of Citrus reticulata extract as well as the impact of this carotenoid-rich extract (CCE) dietary supplementation on the performance, meat quality, and immune-oxidative status of broiler chickens were determined. One hundred and twenty one-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Similarly, it has been suggested that inclusion of orange pulp in broiler diets could potentially reduce MDA levels in broiler meat (Mavrommatis et al, 2022). Moreover, our results are related to those presented by (Petru Alexandru Vlaicu et al, 2020), where broiler diet supplemented with orange pulp had a lower level of TBARS compared to the control group.…”
Section: -Meat Proximate Composition Of Different Chickensupporting
confidence: 90%
“…Similarly, it has been suggested that inclusion of orange pulp in broiler diets could potentially reduce MDA levels in broiler meat (Mavrommatis et al, 2022). Moreover, our results are related to those presented by (Petru Alexandru Vlaicu et al, 2020), where broiler diet supplemented with orange pulp had a lower level of TBARS compared to the control group.…”
Section: -Meat Proximate Composition Of Different Chickensupporting
confidence: 90%
“…Providing lycopene to broiler chickens exerts positive effects ( Table 1 ), especially in crucial periods such as extreme temperature and infection-associated conditions [ 8 ]. The inclusion of a commercial diet supplemented with lycopene has been shown in previous research to boost yolk pigmentation and immunity in chickens throughout production [ 22 , 23 ]. Therefore, this review explains the effects of lycopene in broiler chickens on their performance due to its antioxidant and immune-modulating properties.…”
Section: Introductionmentioning
confidence: 99%
“…Lutein intervention decreased serum MDA and 8-OHdG in rats [ 23 ]. Carotenoid blends including lutein decreased MDA in broilers [ 24 ]. Lutein treatment blocked the high glucose-mediated elevation of intracellular reactive oxygen species, PCO, and MDA content in ARPE-19 cells [ 25 ].…”
Section: Discussionmentioning
confidence: 99%